Competence and Satisfaction in Occupational Performance Among a Sample of University Students: An Exploratory Study. (October 2019) - Keptner, Karen M.; Rogers, Rachel
Success at university may be influenced by concerns with occupation and occupational performance. To understand occupations of concern and occupational performance among a sample ( N = 144) of university students in the Midwest United States, the Canadian Occupational Performance Measure was administered. Socially related ( n = 103), academic-related ( n = 75), and work-related ( n = 64) occupations were the three most frequently reported occupational concerns. Time management ( n = 79) was the most frequent person-level concern. Mean self-perceived competence in occupations was 29.83 ( SD = 7.18) out of 50 and mean performance satisfaction was 26.80 ( SD = 8.01) out of 50. There were no differences in occupational performance across gender, race/ethnicity, class standing, living environment, or work status. However, within participants, there was a significant and clinically relevant difference between performance satisfaction and self-perceived competence in occupation, t (143) = 7.052, p < .0005, d = 0.58. Students have varied occupations that they find important, and future research should explore how occupational performance and performance satisfaction influence university success.